Ritual dance in the Tawahka Indians from Honduras in the 17th century - Cardona Amaya, José Manuel (2022)
Received: 07 de enero de 2022.Approved: 07 de marzo de 2022. This article addresses three testimonies written by missionary priests about ritual dance in the Tawahka in the seventeenth century. The main objective is to discuss the role that this cultural practice had in this indigenous town. From an ethnohistorical approach the texts were compared and it was revealed that the accounts were consistent with each other, and therefore plausible as historical evidence. It was concluded that ritual dance was a complex practice among the Tawahkas, which involved the elaboration of a particular clothing, the consumption of human blood and the use of fire. From the dance, the natives could establish communication with their gods and obtain answers to their questions.